Propuesta pedagógica: Arquitectura I - VI - Risso, Luis; Carasatorre, María Cristina; Martínez, Gabriel Pablo (La Plata : s.n., 2014)
Contenido: v.1: Propuesta pedagógica - v.2: Plan de actividades
T.1 . Propuesta pedagógica -- T.2 . Plan de actividades
Keywords: PROPUESTA PEDAGOGICA; ENSEÑANZA; EDUCACION UNIVERSITARIA; CONCURSOS; LA PLATA; FAU; 2014; ARQUITECTURA; RISSO-CARASATORRE-MARTINEZ